Análisis, Diseño e Implementación de un Sitio Web para la exposición de trabajos de los Diseñadores Gráficos de la UNACH - Ortega Quijozaca, Galo Andrés (2024)
Web design is an activity that consists of planning, designing, maintaining and creating web pages, which provide valuable information and services for users who use the web, and these are essential for the positioning of businesses, companies or individuals. Therefore, it is important to take advantage of this tool for the diffusion of content of UNACH’s graphic designers. The objective of this project was to develop and implement a website for the exhibition of graphic design works of UNACH’s designers, and thus promote the work they do. In the actuality, it is vital to have new alternatives to publicise the projects that the graphic designers have created. A qualitative approach was used for the research with which the current situation, the qualities, and channels of diffusion that designers use to exhibit their work were analysed, at the same time through the quantitative research we gathered relevant information from the target audience to know the means of communication they use to find the graphic pieces of UNACH's designers. Descriptive research was used with the objective of collecting information and characteristics of individuals seeking information about the designers’ graphic pieces, field research surveys were conducted to help with data collection to determine the which media channels are used for the exhibition of graphic pieces of UNACH’s designers. The results of the research indicate that the creation of a website for the exhibition of UNACH’s graphic designers works was needed, this website will be a mean of communication so that the public can see the professional work of UNACH’s graphic designers. Consequently, a host and domain on the Internet were assigned, fulfilling the parameters of design and usability found in the study.